Pengaruh Permainan Dakon Terhadap Kemampuan Berhitung Siswa Kelas 1 di SD Negeri 01 Bandardawung Tawangmangu Tahun Ajaran 2016 / 2017 - Nurul Haq, Saidah, Drs. Suwarno,SH,M.Pd (2017)
The aim of the study is to determine the increase dakon game against numeracy Elementary School first grade students 01 Bandardawung. This type of research is quantitative research experiment. The subjects were students of class I SD Negeri 01 Bandardawung Academic Year 2016 / 2017. The results obtained t in the control group of 686 with a significant level of 25% <of ttabel 2,078, so there is no significant improvement for the experimental group obtained sednagkan t 2.259 with significance level of 0,25%> ttable 2.064, resulting in a significant increase. Dakon so the game can improve numeracy skills of students significantly.